Wiener–Hopf analysis of diffraction of acoustic waves by a soft/hard half-plane - Ayub, M.; Mann, A.B.; Ahmad, M.; Tiwana, M.H. (Archives of Mechanics, 2010)
In this paper, firstly, the far field due to a line source scattering of acoustic waves by a soft/hard half-plane is investigated. It is observed that if the line source is shifted to a large distance, the results differ from those of [16] by a multiplicative factor. Subsequently, the scattering due to a point source is also examined using the results of line source excitation. Both the problems are solved using the Wiener–Hopf technique and the steepest descent method. Some graphs showing the effects of various parameters on the diffracted field produced by the line source incidence are also plotted.